2011
DOI: 10.1075/lab.1.3.04arm
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internal and external factors on linguistic performance in the home language and in L2 among Russian-Hebrew and Russian-German preschool children

Abstract: This paper evaluates the contribution of external background factors which pertain to the child’s environment (e.g., parent education, parent occupation, family size, etc.), and internal ones which reflect the child’s time related experience with language (e.g., chronological age, age of L2 onset, etc.) to the development of linguistic skills in the two languages of bilingual children. 65 Russian-German (Mean age: 66mo, Range: 47-86mo) and 78 Russian-Israeli migrant children (Mean age: 70mo, Range: 58-81) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
73
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 14 publications
12
73
3
2
Order By: Relevance
“…L1 input is usually reduced and significantly determines the development of this language. This has been shown by several studies exploring the influence of input parameters on L1 development in ratings of general language skills (De Houwer, 2007) and lexical (Pearson et al, 1997;Klassert and Gagarina, 2010;Armon-Lotem et al, 2011;Hoff et al, 2012) or grammatical skills (Gutiérrez-Clellen and Kreiter, 2003;Gathercole and Thomas, 2009;Klassert and Gagarina, 2010;Armon-Lotem et al, 2011;Hoff et al, 2012;Thomas et al, 2014;Flores and García, 2017;Rodina and Westergaard, 2017).…”
Section: Impact Of L1 Input and Background Factors On L1 Developmentmentioning
confidence: 80%
“…L1 input is usually reduced and significantly determines the development of this language. This has been shown by several studies exploring the influence of input parameters on L1 development in ratings of general language skills (De Houwer, 2007) and lexical (Pearson et al, 1997;Klassert and Gagarina, 2010;Armon-Lotem et al, 2011;Hoff et al, 2012) or grammatical skills (Gutiérrez-Clellen and Kreiter, 2003;Gathercole and Thomas, 2009;Klassert and Gagarina, 2010;Armon-Lotem et al, 2011;Hoff et al, 2012;Thomas et al, 2014;Flores and García, 2017;Rodina and Westergaard, 2017).…”
Section: Impact Of L1 Input and Background Factors On L1 Developmentmentioning
confidence: 80%
“…). Similarly, whereas chronological age has been shown to lead to improvement of HL performance (e.g.,Armon-Lotem, Walters, & Gagarina, 2011;Flores, 2015;Flores, Santos, Jesus, & Marques, 2017), other studies have found no or…”
mentioning
confidence: 89%
“…The literature on language development of bilingual children has consistently shown that one of the most important languageexternal factors predicting bilingual language acquisition is the amount of exposure (Gathercole and Thomas, 2005;Guiberson et al, 2006;Armon-Lotem et al, 2011;Blom and Vasić, 2011;Chondrogianni and Marinis, 2011;Paradis, 2011;Anderson, 2012;Unsworth, 2013Unsworth, , 2015Paradis and Jia, 2016, among many others). In a setting with one dominant societal language and a minority language, a child's input is typically divided between the two languages and comes from two main sources: home and school.…”
Section: Language-external Factorsmentioning
confidence: 99%
“…2 Some varieties of Norwegian still have a traditional three-gender system of masculine, feminine, and neuter, but many dialects have lost the feminine, including the dialects where data collection took place (Oslo and Tromsø). the acquisition of gender (Gathercole and Thomas, 2005;Armon-Lotem et al, 2011;Chondrogianni and Marinis, 2011;Paradis, 2011;Unsworth et al, 2014;Mitrofanova et al, 2018). The amount and quality of input is related to the success or failure in language acquisition (for an overview see Armon-Lotem and Meir, 2019).…”
Section: Introductionmentioning
confidence: 99%